DISCOVERY OF NA- AND ZN BEARING SPINEL IN THE ROCK CUTTINGS FROM THE MAIN HOLE, CHINESE CONTINENTAL SCIENTIFIC DRILLING (CCSD) PROJECT - Ren Y.F.; Zhang Z.M.; Yang J.S.; Shu J.F.; Mao H.K. (My University, 2006)
In the rock cuttings from the main hole, CCSD, Na- and Zn bearing spinel occurred as exsolution lamella in ilmenite and magnetite. The mineral is about 5 ~ 60μm in width and 2 ~ 3μm in length, composed of MgO 17.143 ~ 22.337wt%, Al2O363.646 ~ 66.492wt%, FeO 9.784 ~ 13.924wt%, ZnO 1.649 ~ 6.386wt%, Na2O 0.029 ~ 0.219wt%, where Na2O and ZnO are positively in different grains. By x-ray analysis of synchrotron light source, the spinel is cubic symmetry with space group of Fm3m and crystal cell parameter of a = 0.83781 nm. With the fact that the spinel is associated with ilmenite, magnetite, garnet (pyr = 50 ~ 58mol%) and the garnet is retrograded into orthopyroxene and Mg-chlorite, the spinel should be derived from ultramafic, and experienced amphibolite facies metamorphism. The phenomenon of miscibility gap and exsolution texture are widely occurred in the oxide minerals between Mt-Usp, Mt-Spl and Mt-Ilm. According to the known petrologic experiments of Mt-Usp binary system and Ilm-Gk-Hem ternary system, the oxygen fugacity of the rocks in the main hole is low and forming temperature is at least over 720°C. The ferro-titanium oxides exsoluted during ultramafic magma crystallization, but later in ultrahigh pressure metamorphism may be formed solid solutions and exsoluted again after temperature decrease.
Keywords: CCSD; EXSOLUTION; NA- AND ZN BEARING SPINEL; OXIDE; UHP; ULTRAMAFIC